The role of government in agricultural innovation: Lessons from Bolivia - Hartwich, Frank; Jansen, Heinz-Gerhard (International Food Policy Research Institute, 2007)
Many governments in developing countries attempt to foster agricultural development and innovation by setting up funding facilities, extension programs, and research centers and by subsidizing private-sector and farm activities through fiscal measures. However, when trying to manage complex innovation processes involving many and different actors, governments sometimes find it difficult to design effective interventions and therefore end up supporting and managing only the public research and extension organizations that directly depend upon them. With the aid of various donors, Bolivia introduced a scheme in 2001—the Bolivian Agricultural Technology System (SIBTA)—by which government support to agricultural research and extension was partly delegated to regional semiautonomous foundations. This brief presents the results of a study on the role of the Bolivian government in guiding and managing SIBTA. The study found that despite a number of weaknesses related to the design of the system and the government's limited commitment, the regional foundations have been able to effectively identify the demands of small farmers, set priorities, and provide transparency and accountability with regard to funding and decisionmaking. It suggests that instead of micromanaging such foundations, the government should focus on the big picture and conduct policy analysis and strategic planning to identify opportunities for agricultural innovation and set up incentive mechanisms and information networks that support the many actors involved in innovation processes.